2014
DOI: 10.1007/s10508-014-0393-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Aggression Experiences Among Male Victims of Physical Partner Violence: Prevalence, Severity, and Health Correlates for Male Victims and Their Children

Abstract: Although research has documented the prevalence and health correlates of sexual aggression among women who have experienced severe partner violence (PV), no research has documented the parallel issues among male victims of severe PV. Research also suggests that children of female victims of both physical and sexual PV have worse mental health than children of female victims of physical PV only, but no research has assessed the mental health of children whose fathers experienced both physical and sexual PV. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 59 publications
3
42
0
Order By: Relevance
“…In order to test convergent validity, the Sexual Coercion subscale of the Revised Conflict Tactics Scales (CTS2) was used to assess intimate partner victimization in the past year (Straus et al, 1996). Previous research found that CTS2-SC scores were positively related to psychiatric symptoms in men and a history of physical assault victimization (Hines & Douglas, 2016). The CTS2 contains 14 paired items assessing victimization and perpetration for the same behavior.…”
Section: Ses-sfvmentioning
confidence: 99%
“…In order to test convergent validity, the Sexual Coercion subscale of the Revised Conflict Tactics Scales (CTS2) was used to assess intimate partner victimization in the past year (Straus et al, 1996). Previous research found that CTS2-SC scores were positively related to psychiatric symptoms in men and a history of physical assault victimization (Hines & Douglas, 2016). The CTS2 contains 14 paired items assessing victimization and perpetration for the same behavior.…”
Section: Ses-sfvmentioning
confidence: 99%
“…Despite this gendered understanding, a growing body of both qualitative and quantitative research has found a large number of men are victimized by their intimate partners (Desmarais et al, 2012; Douglas & Hines, 2011; Lysova et al, 2019). Research shows that men suffer from various types of IPA, including physical violence and abuse, psychological, financial, sexual, and legal and administrative abuse, parental alienation, and homicide (e.g., Harman et al, 2016; Hines & Douglas, 2016). For example, the U.S. National Intimate Partner and Sexual Violence Survey (NISVS) found that the annual prevalence of physical victimization in the intimate relationships was 4.0% among women compared to 4.7% among men (Breiding, 2014), while the 2014 General Social Survey on Victimization in Canada found that the number of men who reported to have experienced physical or sexual violence in ongoing intimate relationships in the past 5 years significantly exceeded that of women (2.9% and 1.7%, respectively; Lysova et al, 2019).…”
mentioning
confidence: 99%
“…Indeed, much of the existing literature around men’s victimization has focused on women’s use of physical violence within the relationship (e.g., Hines & Douglas, 2010), as well as highlighting women’s use of coercive and controlling behaviors (Bates et al, 2014; Bates & Graham-Kevan, 2016). However, only a small body of scholarship has explored the range of abuse experienced by men (see Hines et al, 2007), and very little has considered the possibility of sexual violence occurring in this context (see, for example, Hines & Douglas, 2016; Weare & Hulley, 2019). The analysis here points to relationships existing between the different forms of abuse experienced by men.…”
Section: Discussionmentioning
confidence: 99%
“…One of the only studies to have specifically explored the experiences of men who have been subjected to sexual aggression from a female partner within an abusive relationship originates in the United States. Hines and Douglas (2016) found that over half of the men in their sample of 611 had experienced some form of sexual aggression within their relationship, with 28% having experienced what the authors described as “severe” sexual aggression (e.g., threats or force to engage in vaginal, oral and/or anal sex). This article therefore makes an original contribution to knowledge by considering sexual violence as a form of domestic abuse in men’s experiences of female-perpetrated IPV.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation